Effects of Upgrade Versus De Novo Cardiac Resynchronization Therapy on Clinical Response and Long-Term Survival: Results from a Multicenter Study. (February 2017) - Vamos, Mate; Erath, Julia W.; Bari, Zsolt; Vagany, Denes; Linzbach, Sven P.; Burmistrava, Tatsiana; Israel, Carsten W.; Duray, Gabor Z.; Hohnloser, Stefan H.
Abstract : Background—: Benefits of cardiac resynchronization therapy (CRT) on morbidity and mortality in selected patients are well known. Although the number of upgrade procedures from single- or dual-chamber devices to CRT is increasing, there are only sparse data on the outcomes of upgrade procedures compared with de novo CRT. This study aimed to evaluate clinical response and survival in patients receiving de novo versus upgrade CRT defibrillator therapy. Methods and Results—: Prospectively collected outcome data were compared in patients undergoing de novo or upgrade CRT defibrillator implantation at 3 implant centers in Germany and Hungary. Clinical response was defined as an improvement by at least one New York Heart Association (NYHA) functional class. CRT implantation was performed in 552 consecutive patients of whom 375 underwent a de novo and 177 an upgrade procedure. Upgrade patients were more often implanted for secondary prevention, suffered more often from atrial fibrillation, chronic kidney disease, diabetes mellitus, and dyslipidemia, and had more often a non-LBBB (left bundle branch block) wide QRS complex, and lower left ventricular ejection fraction. Upgrade procedures were associated with a lower response rate compared to the de novo group (57% versus 69%, P univariate=0.008, P multivariate=0.021). During the follow-up of 37±28 months, survival was worse after upgrade compared with de novo CRT defibrillator implantations (hazard ratio, 1.65; 95% confidence interval, 1.22–2.24; P =0.001) even after careful adjustment for important baseline variables (adjusted hazard ratio, 1.68; 95% confidence interval, 1.20–2.34; P =0.002) and after propensity-score matching (propensity-adjusted hazard ratio, 1.79; 95% confidence interval, 1.08–2.95; P =0.023). Conclusions—: Both clinical response and long-term survival were less favorable in patients undergoing CRT upgrade compared to de novo implantations. Abstract : Supplemental Digital Content is available in the text.